Lifestyle behaviour of future medical professionals in a tertiary care institute in north-eastern India: a cross-sectional descriptive study - Dutta, Gitashree; Medhi, Gajendra Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: The incidences of some non communicable diseases like diabetes mellitus, obesity, hypertension and cardiovascular diseases have been rising in the country since last few decades due to the unhealthy lifestyle of the people. Researches conducted among medical and nursing students shown that even though they are aware about the consequences of practicing unhealthy lifestyle but still they do not follow the suggested guidelines for healthy lifestyle. To assess lifestyle behaviour related to dietary pattern, physical activity, substance use, sleep, stress management, among MBBS and nursing students. NEIGRIHMS, a tertiary care institute in the capital city of the north-eastern state of Meghalaya, Shillong. Methods: A cross-sectional study was conducted among 313 participants by using a pre-tested self-administered questionnaire. The data was analyzed using the software Statistical package for social sciences (SPSS) 21 version. Results: In this study, 189 (60.4%) students reported sedentary activity of spending ≥2 hours per day on phone, tablets, laptops, television, computers, etc and majority of them (59.7% and 57.2%) use the gadgets for social and whatsapp messaging respectively. Only 18 (5.8%) participants had reported regular physical activity (5 times a week) when asked about the previous month. Conclusions: Sedentary lifestyle, lack of any physical activity, use of gadgets like mobiles, laptops, etc for activities like social media, Whatsapp, unhealthy eating habits were found to be prevalent among the medical students.